2010
DOI: 10.1242/dev.053447
|View full text |Cite
|
Sign up to set email alerts
|

Hox11 genes establish synovial joint organization and phylogenetic characteristics in developing mouse zeugopod skeletal elements

Abstract: SUMMARYHox11 genes are essential for zeugopod skeletal element development but their roles in synovial joint formation remain largely unknown. Here, we show that the elbow and knee joints of mouse embryos lacking all Hox11 paralogous genes are specifically remodeled and reorganized. The proximal ends of developing mutant ulna and radius elements became morphologically similar and formed an anatomically distinct elbow joint. The mutant ulna lacked the olecranon that normally attaches to the triceps brachii musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…For example, in contrast to patella development, Mikic et al reported that the plantar tarsal sesamoids do not form in paralyzed chicks (Mikic et al, 2000). Moreover, there is a growing body of evidence suggesting that early patterning genes, such as Hox9 (Fromental-Ramain et al, 1996), Hox10 (Carpenter et al, 1997), Hox11 (Koyama et al, 2010;Small and Potter, 1993) and Tbx4 (Bongers et al, 2004) affect other aspects of sesamoid development such as their number, distribution and size.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in contrast to patella development, Mikic et al reported that the plantar tarsal sesamoids do not form in paralyzed chicks (Mikic et al, 2000). Moreover, there is a growing body of evidence suggesting that early patterning genes, such as Hox9 (Fromental-Ramain et al, 1996), Hox10 (Carpenter et al, 1997), Hox11 (Koyama et al, 2010;Small and Potter, 1993) and Tbx4 (Bongers et al, 2004) affect other aspects of sesamoid development such as their number, distribution and size.…”
Section: Discussionmentioning
confidence: 99%
“…Why CTGF ablation only affects the zeugopod region could be due to changes in skeletal patterning, mechanobiological alterations, or a combination of the two. One of the key classes of genes involved in limb development includes the Hox genes, and it has been shown that specific mutations in Hoxa11, Hoxc11, and Hoxd11 deleteriously affect normal development of the zeugopod (Wellik and Capecchi, 2003; Zakany and Duboule, 2007; Koyama et al, 2010). Mechanobiological cues are also important in proper limb development, where muscle-induced mechanical load is necessary for proper bone formation in utero (Nowlan et al, 2007, 2008, 2010, 2012; Sharir et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The morphological changes are well known, but the molecular controls are still being elucidated. The location of joints is presumably specified by specific HOX gene expression, particularly Hox11A, Hox11C, and Hox11D, that is required for proper joint formation (Koyama et al, 2010). The differentiation of the joint is first indicated by the expression of Wnt14, a factor necessary for joint development (Hartmann and Tabin, 2001;Garciadiego-C azares et al, 2004).…”
Section: Development Of the Articular Jointmentioning
confidence: 99%